THE INFLUENCE OF SOCIAL MEDIA ON ADOLESCENT SEXUAL EXPLORATION AND SEXUAL BEHAVIOR: SCOPING REVIEW - Ermiati, Ermiati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Adolescents are a vulnerable group to the influence of social media, particularly in sexual exploration and behavior. This study aims to examine the literature on the influence of social media on adolescent sexual behavior through a scoping review approach. A literature search was conducted across six databases using keywords related to